Identification of Primary and Secondary Metabolites of Apis cerana Honey using FTIR-ATR Diamond Spectroscopy and Their Botanical Origin - Lestari, Tiffany Hanik; Susandarini, Ratna (Biology, Medicine, & Natural Product Chemistry, 2023)
Apis cerana Fab. is one of the popular honeybees species among beekeepers in Indonesia. This species is easy to care for and produces valuable honey products. Honey from A. cerana is abundantly available in traditional and modern markets in Indonesia. The purpose of this study was to identify the primary and secondary metabolites in the honey produced by A. cerana using FTIR-ATR Diamond spectroscopy. Twelve samples of honey from three provinces in Java Island were used in this study. In general, all honey samples contained protein, carbohydrate, water, alcohol, cellulose, alkaloid, tannin, and flavonoid. Variation on primary and secondary metabolites in honey samples was strongly affected by the botanical origin, geographical origin, and the local condition around beekeeping areas where the honeycombs were placed.